Graduate income and profession linkage: Tracer study of public relations graduates - Lukman, Syauqy; Rizal, Ii; Tiara, Olga (PRofesi Humas, 2023)
Background: Higher educational institutions must prepare graduates for careers by monitoring their performance. They must also evaluate academic relevancy to practical needs. The PR program at Universitas Padjadjaran strives to deliver the best education and monitor graduates’ performance. Purpose: This paper aims to study how graduates’ first income is associated with GPA, study duration, and job wait time. This study also linked public relations education with graduates’ current position in their work based on their self-assessment. Methods: Using tracer study data from the Career and Development Centre of Universitas Padjadjaran, exploratory data analysis was done to examine the characteristics of graduates based on the observed variables. The bivariate analysis investigated the association between income, GPA, study duration, and job wait time. Conclusion: Findings of this study show no statistical evidence of the relationship between first salary, GPA, and duration of the study. Exploratory data analysis shows that PR program graduates perform well when comparing the average income of undergraduates on a national level. Graduates’ self-assessment of study relevancy indicated that most graduates possess the relevant educational background and appropriate level of education for their current occupational position. As the statistical testing for this study was conducted post hoc, careful considerations need to be taken when taking the results at face value, considering potential flaws in the sampling frame and the power of the tests. Implications: The findings in this study would serve as a platform for future references on graduates or tracer study, more specifically public relations graduates, as it provides a starting point for measuring graduates’ performances. As the database provides more data with more graduates in future years, an updated finding of this particular study would be very important to measure how well graduates fare post-graduation.